Kehidupan Buruh Migran dalam Novel Burung-Burung Migran Karya Miranda Harlan dan Sutik A.S. - Kartika, Lita; Mas Triadnyani, I G.A.A (Humanis; Vol 22 No 1 (2018), 2018)
Novel of Burung-Burung Migran by Miranda Harlan and Sutik A.S. is selected as the object of study for several reasons.  First, BBM novel contains social issues of migrant workers' lives which is reflected in the story. Second, the novel of BBM tells a conflict how hard the lives of the migrant workers who are fighting for survival. The issues discussed are structural and social aspects of the lives of migrant workers contained in the BBM novel. The theory used in this analysis, namely structural theory that emphasizes the elements of the plot, characterization, and setting. Followed by the theory of sociology of literature that prioritizes literary text as a review in accordance with the theory of Sapardi Djoko Damono. Methods and techniques used in this study are three, namely: (1) methods and techniques of data collection, used literature review which methods and techniques used are the techniques of reading, record; (2) methods and techniques of data analysis used descriptive analysis and then proceed with reading and listening techniques; (3) methods and techniques of presenting the results of data analysis described in the format of a good and correct thesis writing. Based on the results of the analysis can be concluded that, according to Nurgiyantoro structure analysis includes three aspects namely, characterization, plot, and setting. Characterization is divided into main character and additional characters. The main character is Sutik, additional characters, namely: Yamin, Mak-Bapak, Asih, A Beng & A Nyi, Chow & Tessa, Bang Man, Sumiati. Characterization includes three elements namely, physiological, psychological and sociological elements. The plot is divided into three stages, namely the initial stage, middle stage, and the final stage. Chronological plot is used in the BBM novel. The setting is divided into three, i.e. the place, time, and social background. Setting of places, including: Indonesia, Singapore, Malaysia, and Thailand. Setting of time is around the year of 1976-2010. Social background tells the society of Tretes Village. The moral aspects of migrant workers that were revealed in this novel is the problem of good and bad moral. The social aspect deals with Sutik's relationship with family, society, and individual. There are two aspects of education, namely formal education and informal education. The cultural aspect describes the behavior of people in Indonesia and in Malaysia. Economic aspects of the BBM novel reveal the problems of changed level of prosperity in the societies in which Sutik’s live in that is Tretes village.